Popular periodicals, common readers and the 'grand march of intellect' in London, 1819-34 - Magee, DSKJ (2008)
Between the 1780s and the 1830s increasing amounts of agency were assigned to - and claimed by - the English common people in their own intellectual improvement and moral reform. In the years between 1819 and 1834, this sense of ‘popular agency’ (the capacity of the common people to assert control over aspects of their lives) was increasingly embodied in - and cultivated by - London’s ‘popular periodical’ press. It was in this popular press (comprising cheap weekly magazines costing three-pence or under and stamped, seven-penny Sunday newspapers - both aimed at ‘common readers’) that the concept of a ‘march of intellect’ was most strongly contested as a narrative of popular intellectual and moral progress, a categorization of knowledge forms and a description of improving practice. This thesis attempts to rethink the ‘march of intellect’ as a socio-political complex through an analysis of its discursive properties and material bases, as revealed in the popular periodical. Asking questions about the origins, nature, timing, reality and significance of the ‘march’, it argues that although the trope was rich raw material for reformist rhodomontade and reactionary satire, it was also a widely-recognized shorthand for a range of experienced imperatives and practices. In this context, the popular press was frequently depicted as cultivating a latent ‘common readership’ of lower-middling and labouring-class Londoners; as making the cultural world of the common people a focus of enquiry; and as providing a medium through which the ‘common writer’ could articulate a sense of personal intellectual agency. This re-imagination of the common reader as an active historical agent was, however, circumscribed by the nature of the popular periodical itself. No simple link between the overall growth of a popular periodical market and the perceived increase in popular agency can therefore be confidently made. This thesis concludes that the march of intellect was the product of a specific historical moment: a linguistic and conceptual framework through which the public image of the common people was being reworked - and a repertoire of practices experienced - in the context of profound economic, technological and demographic changes. Slower and more haphazard than its champions claimed, the ‘march’ was nonetheless the locus of a crucial debate during the ‘age of reform’ about the place of the common people in English society: a debate in which at least some of these people articulated their opinions.